Investigation of comorbid autoimmune diseases in women with autoimmune bullous diseases: An interplay of autoimmunity and practical implications - Meropi Karakioulaki, BSc, MSc, MD; Dedee F. Murrell, BMBCh, FACD, MD, DSc; Aikaterini Kyriakou, MD, MSc, PhD; Aikaterini Patsatsi, MD, MSc, PhD (Wolters Kluwer, 2022)
Autoimmune bullous diseases are a group of skin disorders resulting from an autoimmune reaction against intercellular adhesion molecules or components of the basement membrane of skin and mucosa. Autoimmune disorders often occur in patients with a history of another autoimmune disease and most autoimmune diseases have a striking female predominance. In this review, we aim to analyze the different associations of autoimmune bullous diseases with other autoimmune diseases and highlight the distinctiveness of the female gender in these associations.